Tingkat Kepuasan Pasien Terhadap Pelayanan Informasi Obat di Puskesmas Tamalanrea Jaya - Andi Nurpati Panaungi; Suci Aulia (BORNEO JOURNAL OF PHARMASCIENTECH, 2023)
Understanding patient needs and desires is something that influences satisfaction. To create patient satisfaction, the Community Health Center must create and manage a system to obtain more patients and the ability to retain patients. Drug Information Services (PIO) is an obligation that must be provided by pharmaceutical personnel related to the use of medicines handed over to patients and the use of medicines appropriately, safely and rationally at the request of the public. The aim of this research is to determine the level of patient satisfaction with drug information services at the Tamalanrea Jaya Health Center, Makassar City. The type of research used is non-experimental research with a descriptive research design using quantitative analysis, namely using in-depth data analysis using a questionnaire as an instrument. research. The sample from this research was calculated using the Slovin formula which resulted in 74 samples. Based on the analysis of data obtained from research conducted on 74 respondents, the conclusion was that the level of satisfaction in the dimension of physical evidence (tangibles) was dominated by those who were satisfied, namely 73, 0%, the reliability dimension is dominated by those who are satisfied, namely around 71.6%, the responsiveness dimension is dominated by those who are satisfied, namely 73.0%, the assurance dimension is dominated by those who are satisfied, namely 67, 6%, while the empathy dimension is dominated by those who are satisfied, namely 60.8%.